Medical appointment and its influence on patients' confidence - Magdalena Kozimala; Edyta Guty; Małgorzata Dziechciaż; Lechosław Putowski (Kazimierz Wielki University, 2017)
Introduction Patient's confidence is very important in patient - doctor communication. It is very vital when we talk about efficient medical care because it can improve this care significently. It is particularly important for people who can not contact with it easily. Thanks to watching relations between patient and doctor we can get to know the way the patient judges references of the doctor during his professional activities. The aim of the thesis The aim of these studies was to estimate the level of patient's confidence after the last medical appointment. The studies were made with the help of Anderson and Dedrick scale. Results Patients were satisfied after the appointment when during the examination they could see a telephone and a computer on the desk, medical equipment and other medical things. The doctor was closer than 61 cm from them and patients could not see any physical barriers. During the examination the position of the doctor was open, he used gestures and he was sitting face to face to the patient (angle 180° or 90°). His eyes were at the same level as patient's eyes.  Conclusions The ability of proper communication with the patient is a very important element of medical care. However, it is often underestimated. But efficiency of therapy and efficiency of diagnostics depend on these factors.